PENGARUH KECERDASAN EMOSIONAL DAN KEPERCAYAAN DIRI TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi Kasus Pada Mahasiswa Akuntansi Universitas Islam Malang dan Universitas Widyagama Malang) - Rindit Pranandari; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to determine the influence of emotional intelligence and confidence on the level of accounting understanding both simultaneously and partially. This type of research is correlational research, research that is intended to measure the degree of closeness of relationships between variables. The population in this study includes final-level accounting students of the Faculty of Economics and Business majoring in Accounting semester 8 of the class of 2017 from the Islamic University of Malang and Widyagama University of Malang. The data collection method used in this study is a survey with a questionnaire.The outcome of this study shows that: 1) Emotional Intelligence and Confidence simultaneously affect the Level of Accounting Understanding. 2) Emotional Intelligence has no partial effect on the Level of Accounting Understanding. 3) Confidence partially positively affects the Level of Accounting Understanding..Keywords: emotional intelligence, confidence, and accounting comprehension level.